Removal of Heavy Metal Ions From Aqueous Solutions - noei, maziar; salari, Ali-Akbar; Nafar, Samira; Ebrahimikia, Maryam; Anaraki -Ardekani1, Hosein (Journal of Science and Technology, 2014)
The removal of Zn(II), V(II), by silica aerogel has been found to be concentration, , contact time, adsorbent dose and temperature dependent. ion exchange are the major removal mechanisms involved. The adsorption isotherm studies clearly indicated that the adsorptive behaviour of metal ions on silica aerogel was satisï¬ed. The applicability of the Lagergren kinetic model has also been investigated. Thermodynamic constant (Kad ), standard free energy ( âˆ†G0 ),enthalpy (âˆ†H0 ) and entropy (âˆ†S0 ) were calculated for predicting the nature of adsorption